Expert information processing system for traffic light system decision-making with adaptive conditional tram priority - Lytvynenko, M.; Rebezyuk, L. (ХНУРЕ, 2023)
The article considers the problem of taking into account the dynamics of a tram with a dedicated right of way as it approaches an intersection to provide conditional traffic signal priority with respect to the private transport flow saturation before the intersection. The expert information processing system for the intersection traffic lights system is developed. Decision-making rules regarding the adaptation of the traffic signal plan time parameters based on the interoperability of the signals and their importance have been proposed. The information processing system is implemented and validated using the SUMO urban mobility simulation tool for moderate and saturated transport demands for an artificial intersection